Implementation of a Solar-Powered Air Control System in Broiler Chicken Closed House Farming - Rachmanita, Risse Entikaria; Subagja, Hariadi; Utomo , Denny Trias; Susmiati, Yuana; Widiawan, Beni (P3M Politeknik Negeri Jember, 2025)
Closed-house broiler chicken farming enhances productivity and animal welfare by maintaining optimal environmental conditions. However, reliance on grid electricity for air control systems increases operational costs and environmental impact. This study investigates the implementation of a solar-powered air control system to regulate temperature, humidity, and ventilation in closed-house broiler farming. The system integrates photovoltaic (PV) solar panels, energy storage, and a smart control mechanism. The system's performance is evaluated based on energy consumption, solar energy generation, and environmental parameters. Results show the system effectively maintains optimal broiler growth conditions while reducing energy dependence. Energy savings of up to 10% are achieved, leading to lower operational costs and improved sustainability.The findings demonstrate the feasibility of solar-powered solutions in broiler farming, reducing greenhouse gas emissions and enhancing farm resilience. Future work will explore IoT integration for real-time monitoring and further energy optimization.